Career Orientation for Students Through Teaching STEM Topics of Aldehyde - Carboxylic Acid - Trang, Vu Minh (VNU Journal of Science: Education Research; Vol 38 No 1DO - 10.25073/2588-1159/vnuer.4598, 2022)
The socio-economic development of Vietnam in the context of international integration has set new requirements for education in training dynamic and flexible human resources. Therefore, the general education program needs to be reformed to ensure integration, approach the achievements of modern science, and develop thinking ability, creative logic, and train the ability to apply knowledge into real life. The objectives of the paper are: 1) analyzing the theory of project-based learning, 2) Building evaluation criteria for the ability to apply knowledge into practice, 3) Designing and experimentally organizing two learning projects in Chemistry "Electric batteries and electrolysis" in order to develop the ability to apply knowledge into practice for high school students. The study evaluates the feasibility of two projects for capacity development in experimental and control classes (80 students) of grade 12 of a High school in Hanoi. The results of pedagogical experiment findings show that teaching based on the two projects designed has achieved the teaching objectives. Teaching operated by project- based learning not only helps students acquire knowledge but also develops student`s ability to apply knowledge into practice, contributing to improve the quality of chemistry teaching in high school.